Pueblo boy : growing up in two worlds - Keegan, Marcia (New York : Cobblehill Books, 1991)
Text and photographs depict the home, school, and cultural life of a young Indian boy growing up on the San Ildefonso Pueblo in New Mexico.
Wilson's Children
Elem. School Library Collection
School Library Journal
6.4
3-6
Keywords: Roybal, Timmy; Roybal, Timmy; Pueblo Indians -- Biography -- Juvenile literature; Pueblo Indians -- Social life and customs -- Juvenile literature; San Ildefonso (N.M.) -- Social life and customs -- Juvenile literature; Pueblo Indians -- Biography; Pueblo Indians -- Social life and customs; Indians of North America -- New Mexico -- Biography; Indians of North America -- New Mexico -- Social life and customs; Roybal, Timmy; Pueblo Indians -- Biography; Pueblo Indians -- Social life and customs; Indians of North America -- New Mexico